The Study of The Students’ Ability to Use Punctuation in Writing Skill - Fitrah Yuliawati; Ika Nuriyanti (Universitas Islam Madura, 2017)
Writing is one of the skills in English that should be mastered by students. Writing is means of communication whereby writing transmit idea to the reader. There are many steps in teaching writing skill. One of the steps is the teaching of punctuation. Punctuation is an element that has an important role in writing. Punctuation refers to sign on marks used to clarify the writings’ idea and the readers can understand easily the meaning of the sentences. This research used qualitative research, because this research describes about the students’ ability to use punctuation in writing. The research was conducted at Madura Islamic University. The result of this research found about to what extent students use the punctuation marks. Firstly, external punctuation. Secondly, internal punctuation. thirdly, pairs punctuation. Fourthly, special punctuation.